Peptide Aggregation during Plastein Reaction Enhanced Bile Acid‐Binding Capacity of Enzymatic Chicken Meat Hydrolysates. Issue 3 (27th April 2015) - Udenigwe, Chibuike C.; Mohan, Aishwarya; Wu, Sihong
Abstract Plastein, a product of protease‐induced peptide aggregation, was formed from chicken meat hydrolysates (CMHs) produced with Alcalase, bromelain and pancreatin. Plastein reaction resulted in increased surface hydrophobicity, except for the Alcalase reaction, possibly due to clustering of aggregating hydrophobic peptides. The protease‐induced process resulted in increased capacity of CMH to bind primary, secondary and conjugated bile acids. Although the CMH had similar amino acid compositions, pancreatin hydrolysates and the resulting plastein yielded the highest binding capacity, followed by bromelain. This indicates that factors other than the total hydrophobic amino acid residues, such as surface hydrophobicity, would have contributed to bile acid binding. CMH plastein samples bound more trihydroxyl than dihydroxyl bile acids, which is the opposite of the activity of cholestyramine, a bile acid sequestrant. The findings will promote the design of peptide‐based bile acid‐binding resins from protease‐treated meat products for regulating endogenous lipid levels during hyperlipidemia. Practical Applications Hydrophobic amino acid residues of hydrolysates and peptides are thought to be crucial for bile acid binding. The findings from this study demonstrate that hydrolysates with similar hydrophobic amino acid composition have significantly different activities, and that protease‐induced peptide aggregation can be used to enhance bile acid‐binding capacity. This process can be explored for use in the recovery of meat proteins for the development of peptide‐based nutraceutical resins for the management of hyperlipidemia in humans.